LC-NMR and other hyphenated NMR techniques : overview and applications - Silva Elipe, Maria V., 1963- (Hoboken, NJ : Wiley, 2012)
'This guide provides an overview of the pros and cons of NMR Spectroscopy as hyphenated and non-hyphenated techniques. Chapters are logically ordered in presenting theory (Basics and Historical Background) to applications (Degradation products, Drug metabolism, Food analysis, Drug discovery, and Polymers). The book also contains updated information on the latest advancements and applications of LC-NMR such as degradation products, drug metabolism, food analysis, and Drug discovery. This clear resource offers a practical view for non-experts who need to understand the technology. Examples given are illustrated with figures and detailed explanations'--
Keywords: Nuclear magnetic resonance spectroscopy -- Industrial applications; Organic compounds -- Analysis; Drug development